The roles of resveratrol on cardiac mitochondrial function in cardiac diseases - Apiwan Arinno (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Left ventricular (LV) dysfunction is commonly associated with a variety of health conditions including acute myocardial infarction and obesity/diabetes. In addition, administration of several pharmacological agents such as anticancer, antiviral, and immunosuppressive drugs has been shown to be related with LV dysfunction. The molecular mechanism responsible for LV dysfunction has been extensively studied, and it has been proposed that the overproduction of reactive oxygen species (ROS) plays a crucial role in the regulation of this function. Mitochondria require the balance between ROS production and antioxidants to maintain their appropriate function and to prevent excessive ROS production. Thus, the excessive production of ROS and the reduced scavenging process under any pathological conditions could disrupt mitochondrial function, leading to energy depletion with subsequent cell death. Therefore, maintenance of the balance between oxidative stress and antioxidants is essential. Resveratrol, a stilbene, has been investigated extensively, and potentially used to treat or prevent various cardiovascular diseases. Resveratrol directly upregulates antioxidative capacity by increasing antioxidant genes such as heme oxygenase-1, superoxide dismutase, catalase, and glutathione. In this review, accumulated data from in vitro, ex vivo, and in vivo studies regarding the effects of resveratrol on cardiac mitochondrial function in cardiac pathologies are comprehensively summarized and discussed. Since there is no conclusive available clinical study regarding the effects of resveratrol on cardiac mitochondrial function, this review also aims to encourage more clinical investigations to confirm findings from basic research. This comprehensive review will provide insight regarding the potential mechanistic roles of resveratrol in preventing and/or treating patients with cardiovascular diseases to improve LV function and their health status.